2004
DOI: 10.1063/1.1707213
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear waste disposal—pyrochlore (A2B2O7): Nuclear waste form for the immobilization of plutonium and “minor” actinides

Abstract: During the past half-century, the nuclear fuel cycle has generated approximately 1400 metric tons of plutonium and substantial quantities of the ''minor'' actinides, such as Np, Am, and Cm. The successful disposition of these actinides has an important impact on the strategy for developing advanced nuclear fuel cycles, weapons proliferation, and the geologic disposal of high-level radioactive waste. During the last decade, there has been substantial interest in the use of the isometric pyrochlore structure-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
723
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 997 publications
(774 citation statements)
references
References 140 publications
16
723
0
3
Order By: Relevance
“…The cation and anion sites of Ce 2 Zr 2 O 7 are split in Ce 2 Zr 2 O 8 by lowering the symmetry from Fd 3m to P2 1 3. Cations form distorted CeO 8 and ZrO 8 polyhedra that are connected by shared edges as in fluorite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cation and anion sites of Ce 2 Zr 2 O 7 are split in Ce 2 Zr 2 O 8 by lowering the symmetry from Fd 3m to P2 1 3. Cations form distorted CeO 8 and ZrO 8 polyhedra that are connected by shared edges as in fluorite.…”
Section: Resultsmentioning
confidence: 99%
“…Information obtained from these studies is also valuable regarding their use as a host lattice for transmutation products of reactors and the safe deposition of plutonium. 3,7,8 The high radiation and chemical stability and low neutron absorption coefficients of Zr make zirconate pyrochlores extremely useful for these purposes, but recent studies have found pressure-driven instabilities. 9 Structural transitions were reported for Sm 2 [10][11][12] Studies on related Y 2 Zr 2 O 7 indicated the formation of a defect-cotunnite structure at 18 GPa.…”
mentioning
confidence: 99%
“…During the last two decades, significant efforts have been made to better understand the incorporation of early actinide elements (namely Th, U, Np, and Pu) into a variety of mineral phases, such as calcite (7)(8)(9)(10)(11)(12)(13)(14)(15), zircon (4,(16)(17), monazite (4,(17)(18), zirconolite (4,(18)(19)(20)(21)(22), perovskite (4,22), garnet (4), pyrochlore (4,(23)(24)(25), brucite (26), and several other systems (27)(28)(29)(30). Particularly for transuranium elements (Np and Pu), it was determined that these can also be incorporated into a series of uranium-or thorium-based minerals such as brannerite (4), ianthinite (31), schoephite, becquerelite, compreignacite, and boltwoodite (32) or even synthetic phases such as Th 2-x/2 An IV x/2 (PO 4 ) 2 (HPO 4 )·H 2 O (An = U, Np, Pu) (33), ThSiO 4 (34), and Ba 3 (UO 2 ) 2 (HPO 4 ) 2 (PO 4 ) 2 (35).…”
Section: Introductionmentioning
confidence: 99%
“…Today about 1400 tons of plutonium exists worldwide; about 300 tons in military installations, 200 tons have been used for fabrication of mixed oxides (MOX) nuclear fuel and about 900 tons is stored in power plants [1]. Taking into account that the fabrication of a nuclear warhead requires less than 10 kg of plutonium and that one 1000 MW reactor produces something like 200 kg of 239 Pu per year it becomes clear that the problem of excess plutonium must be rapidly solved.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account that the fabrication of a nuclear warhead requires less than 10 kg of plutonium and that one 1000 MW reactor produces something like 200 kg of 239 Pu per year it becomes clear that the problem of excess plutonium must be rapidly solved. Two strategies are currently envisaged; (i) the use of 239 Pu as a nuclear fuel in new generations of reactors and (ii) direct disposal of spent nuclear fuel (SNF) in geological repositories [1][2][3]. In the first case fissile isotopes have to be embedded in a special material, called inert matrix fuel (IMF), in the second scenario SNF must be transformed into a stable form which can be permanently disposed.…”
Section: Introductionmentioning
confidence: 99%